130k views
5 votes
Given the function defined below, what is the value of the 4th term?

f (1) = -4
f (n) = -3f (n-1) +5
f (4) =

User Gangadhar
by
5.1k points

1 Answer

4 votes

Answer:

The 4 t h term is f(4) = 143

Explanation:

Explanation:-

Given function f(1) = -4

Given 'nth' term is f(n) = -3f(n-1) +5

Put n =2 f(2) = -3 f(2-1) +5

= -3 f(1) +5

= -3 (-4) +5

= 12 +5

f(2) = 17

put n= 3

f(n) = -3f(n-1) +5

f(3) = -3 f(3-1) +5

= -3f(2) +5

= -3(17) +5

= -51+5

f(3) = -46

Put n=4

f(n) = -3f(n-1) +5

f(4) = -3f(4-1) +5

f(4) = -3f(3)+5

f(4) = -3(-46)+5

f(4) = 138 +5

f(4) = 143

Final answer:-

The 4 t h term is f(4) = 143

User YanDatsiuk
by
5.7k points